Islamic Management and Leadership in the Organization of the Indonesian Ulama Council Padangsidimpuan, Indonesia - Jambak, Dakran; Fauzan ROYHANUDDIN; Syafnan (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study aims to analyze the application of Islamic management and leadership principles in the Indonesian Ulema Council (MUI) organization in Padangsidimpuan City. Using descriptive qualitative methods and a phenomenological approach, this study explores the meaning and experiences of MUI members related to the implementation of Islamic values, such as justice, trustworthiness, social responsibility, and deliberation. The results of the study indicate that the application of Islamic management and leadership in MUI Padangsidimpuan has increased the effectiveness of organizational performance, strengthened the integrity of members, and the relevance of programs to community needs. However, challenges in the form of differences in internal views and limitations in the implementation of deliberation are still faced. This study is expected to provide theoretical contributions to the study of Islamic management and practical recommendations for the development of organizations based on Islamic values.